Religion, extremism, violence - Danilov, Andrey V. (Journal of the Belarusian State University. Sociology, 2019)
Extremism is associated with the political ambitions of gaining power through violence. Such ambitions can also be present in religion, especially if it imposes universalist claims. There is religiously motivated extremism in the movements for which the conception of the impossibility of tolerant attitude to other religious forms and views is typical. Religious extremism, exemplified by Islamism today, is directed toward establishing a theocracy, not a political dictatorship. Constantly ready for violence, religious extremism is drifting towards religious terrorism, which is an aggressive violent act against people who disagree with extremists. Violence serves religious, political or ideological purposes, and terrorism is a mean of putting pressure.
Keywords: religious identity; radicalization; extremism; violence; Islamism; conflicts; fundamentalism